Efeito do bicarbonato de sódio no desempenho físico: revisão - Caversan, Rodrigo Cintra [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The current study had the objective to gather and introduce the recent studies about the use of sodium bicarbonate (NaHCO3) as a supplement to improve athletic performance in high intensity sports. The purpose of this review was to present and clarify the protocols used in the research and the guidelines that are most accepted in the literature, analyzing the physical and physical characteristics of NaHCO3 in the performance of physical movements, mainly with the lactic anaerobic characteristic, associated to several sports modalities. The studies that were done later the last systematic reviews related to the subject were collected in the PubMed database (carried out in 2015 and 2016) until October 2018. Studies that included NaHCO3 as the main ergogenic for performance improvement were analyzed and included, studies that included other supplements or combinations with NaHCO3, such as beta alanine, sodium citrate and caffeine were excluded from the analysis. Also excluded were those studies that presented as sport, sports characterized as predominantly aerobic. A total of 30 studies were analyzed, from the beginning 11 were excluded by the reading of the title, and 5 later by reading the abstract. Finally, 14 studies were used, in which the NaHCO3 dosage was used, the time of ingestion up to the execution of the exercise itself, the way it was administered, the participants and their characteristics, as well as which exercises were performed in the studies. The results show that, to obtain an improvement in the performance of physical exercises, NaHCO3 should be consumed prior to exercise, in approximately 60 to 90 minutes before carrying out the proposed activity. When it comes to dosage, it is a consensus among most studies that an acute amount greater than 0.3g/kg body weight of NaHCO3 can bring gastrointestinal discomfort to the individual and thus does... (Complete abstract electronic acess below)

O presente estudo teve por objetivo reunir e apresentar os recentes estudos sobre a questão do uso do bicarbonato de sódio (NaHCO3) como suplemento para melhora no desempenho atlético em esporte de alta intensidade. O intuito desta revisão foi apresentar e esclarecer sobre os protocolos utilizados nas pesquisas e as orientações que são mais bem aceitas na literatura, analisando os efeitos da suplementação de NaHCO3 no desempenho de exercícios físicos, principalmente com característica anaeróbica láctica, associados a diversas modalidades esportivas. Foram levantados na base de dados PubMed os estudos que vieram posteriormente às últimas revisões sistemáticas relacionadas ao tema (realizadas no ano de 2015 e 2016) até outubro de 2018. Foram analisados e incluídos os estudos que apresentavam o NaHCO3 como o principal ergogênico para a melhora no desempenho, ou seja, estudos que incluíam outros suplementos ou combinações com o NaHCO3, como beta alanina, citrato de sódio e cafeína foram excluídos da análise. Também foram excluídos aqueles estudos que apresentavam como modalidade esportiva, esportes caracterizados como predominantemente aeróbico. Um total de 30 estudos foram analisados, de início foram excluídos 11 pela leitura do título, e mais 5 posteriormente pela leitura do resumo. Por fim, foram utilizados 14 estudos, nos quais foi observada a dosagem utilizada de NaHCO3, o tempo da ingestão até a execução do exercício em si, a maneira como foi administrada, os participantes e suas características, bem como quais exercícios eram realizados nos estudos. Os resultados mostram que, para obtenção da melhora no desempenho dos exercícios físicos, o NaHCO3 deve ser consumido previamente ao exercício, em aproximadamente 60 a 90 minutos antes da realização da atividade proposta... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Bicarbonato de sódio; Suplementos dieteticos; Desempenho; Sodium bicarbonate